2019
DOI: 10.1016/j.jvir.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation of Four Types of Drug-Eluting Embolics Loaded with Idarubicin

Abstract: This study compared loading, elution, and stability of drug-eluting embolic beads (DEBs) loaded with idarubicin. Materials and Methods: DC Bead (100-300 μm), HepaSphere (30-60 μm), LifePearl (200 μm), and Tandem (100 μm) DEBs were loaded with 5 mg/mL idarubicin. Loading, elution, diameter changes, loading stability over 2 weeks in storage, and time in suspension were determined for each of the DEBs. Results: Loading of more than 99% of idarubicin was achieved within 15 minutes for LifePearl, DC Bead, and Tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…The release profiles of CalliSpheres ® with 20 mg of IDA loaded in PBS and PBS + 10% FBS are shown in Figure 3. The IDA concentration in the control group decreased during the experiment, which was consistent with previous reports [8]. The results reveal that CalliSpheres ® had a sustained release ability, and the release rate decreased with an increase in the CalliSpheres ® particle sizes.…”
Section: Ida Release Profilessupporting
confidence: 91%
See 1 more Smart Citation
“…The release profiles of CalliSpheres ® with 20 mg of IDA loaded in PBS and PBS + 10% FBS are shown in Figure 3. The IDA concentration in the control group decreased during the experiment, which was consistent with previous reports [8]. The results reveal that CalliSpheres ® had a sustained release ability, and the release rate decreased with an increase in the CalliSpheres ® particle sizes.…”
Section: Ida Release Profilessupporting
confidence: 91%
“…The application of IDA in TACE has been proved by previous studies [4,5], which have also revealed some advantages that IDA might have in HCC therapy [6,7]. Some previous studies have investigated the ability to load IDA to classic embolic beads [8], such as DC Bead TM (BTG, Surry, UK) and HepaSphere TM (Merit Medical, South Jordan, UT, USA). However, the detailed IDA loading profiles, such as dosage, concentration, and drug loading time and medium, have not been studied clearly.…”
Section: Introductionmentioning
confidence: 99%
“…HepaSphere® and DC bead, the size of DEB after anticancer loading and time in drug elution were shown to be different between each DEB. 36 In an in vivo model, HepaSphere® was shown to induce higher local concentration of anticancer drug compared with DC bead. 37 Furthermore, we could not show the differences of antitumor effect between epirubicin and arterial cisplatin in the present study.…”
mentioning
confidence: 99%
“…During the last 10–15 years, we witnessed the development and clinical introduction of so‐called drug‐eluting beads (DEBs) to be used in TACE 14 . These are embolic polymer microspheres loaded with a chemotherapeutic agent, such as doxorubicin, irinotecan, idarubicin, and sunitinib 15‐26 . A particularly attractive feature of drug‐eluting embolic beads (DEB‐TACE) is that toxic side‐effects of the drug to healthy parts of the body are largely avoided.…”
Section: Introductionmentioning
confidence: 99%
“…14 These are embolic polymer microspheres loaded with a chemotherapeutic agent, such as doxorubicin, irinotecan, idarubicin, and sunitinib. [15][16][17][18][19][20][21][22][23][24][25][26] A particularly attractive feature of drug-eluting embolic beads (DEB-TACE) is that toxic side-effects of the drug to healthy parts of the body are largely avoided. Such side-effects frequently become very problematic when chemotherapeutics are administered systemically (e.g., via intravenous injection).…”
Section: Introductionmentioning
confidence: 99%